Mooi Street and other moves - Slabolepszy, Paul, 1948- (Wits University Press, 2017)
This collection of six plays by one of South Africau2019s leading playwrights/actors features works written between 1984 and 1993. Slabolepszy, who has won many awards in South Africa and abroad both for his plays and his performances in them, is a master of dialogue, capturing the essence of the personality and speech patterns of his protagonists in language that is often dramatic, frequently funny, sometimes tragic and always entertaining. The works included are Under the Oaks, Over the Hill, Boo to the Moon, Smallholding, Mooi Street Moves and The Return of Elvis du Pisanie. Elvis won Slabolespzy the 1992/93 IGI Life Vita Award for Play of the Year and, together with Mooi Street Moves, gained him the Vita Playwright of the Year award. This collection is introduced by Robert Greig, a well-known theatre critic, and by Bobby Heaney who has been involved in the evolution of several of Slabolepszyu2019s plays.